IDENTIFIKASI TANTANGAN PERAN GURU DALAM PEMBELAJARAN KURIKULUM MERDEKA DI SEKOLAH DASAR - Sulthan Saladin Usman; Fidrayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to identify the challenges faced by the role of teachers in implementing independent curriculum learning in elementary schools using a descriptive qualitative approach. The research method used was in-depth interviews and observations of teachers in elementary schools that implemented the independent curriculum. Research findings show that there are several challenges faced by teachers, such as lack of time to adapt the independent curriculum, limited resources, and minimal training provided to teachers. It is hoped that this research can provide in-depth insight into the challenges faced by teachers in implementing the independent curriculum in elementary schools, so that they can provide appropriate recommendations to improve the quality of learning.   Keywords: elementary school, independent curriculum, teacher challenges